Сон о свободе: школа Марины Абрамович (О перформансах Деспины Захаропулу, Сандры Джонстон и Александра Тимотича в рамках арт-события «Захват») - Jeknič, Lana (Wiener Slawistischer Almanach, 2025)
This article analyses the performances of three artists, who have inherited Marina Abramović‘s performance art tradition – Despina Zacharopoulou, Sandra Johnston and Aleksandar Timotić. Their works were performed as part of the artistic event “Takeover ˮ in London (Southbank Center) from the 4th to 8th of October, 2023. The entire building was transformed into an artistic platform for the performances for a total duration of more than tweinty-eight hours. These are long durational performances, the practice of which is nurtured by the Marina Abramović Institute, and which are aimed at the inner work and change of both the performer and the audience that participates in the performance.